Electrochemically Triggered Chain Reactions for the Conversion of Furan Derivatives. Issue 14 (24th February 2021) - Chen, Rong; Yang, Cangjie; Zhou, Zefeng; Haeffner, Fredrik; Dersjant, Alinda; Dulock, Nicholas; Dong, Qi; He, Da; Jin, Jing; Zhao, Yanyan; Niu, Jia; Wang, Dunwei
Abstract: We report an electrochemical method for coupling biomass‐derived C5/C6 compounds to value‐added fuel precursors. Using only 2 % of equivalent charges, 2‐methylfuran (2‐MF) was oxidized to yield a cation radical, which readily reacted with 3‐hexene‐2, 5‐dione, a derivate of 2, 5‐dimethylfuran, to produce 3‐(5‐methylfuran‐2‐yl)hexane‐2, 5‐dione. The product was converted to 4‐ethylnonane (a component of biodiesel/jet fuel) in a single step in excellent yield. Importantly, the reaction was not sensitive to oxygen, and a trace amount of water was found to promote the reaction. Detailed mechanistic studies confirmed the proposed reaction pathways. Key to the mechanism is the radical generation that is enabled by electrochemistry. The radical is regenerated at the end of a reaction cycle to ensure chain propagation for an average of ca. 47 times, resulting in an apparent Faradaic efficiency of 4700 %. Abstract : A new method is developed to enable electrochemically triggered chain reactions for the conversion of biomass derivatives to fuel additives. Only 2 % equivalent charges are consumed, yielding an apparent Faradaic efficiency of 4700 % in terms of hydrocarbon products, whereas the only byproduct is H2 at the cathode. The reaction shows no sensitivity to oxygen from ambient air; trace amounts of water facilitate the reaction by stabilizing a key intermediate.